The Use of N-Terminal-Pro-BNP in Preterm Infants - Afif EL-Khuffash; Eleanor Molloy (Hindawi Limited, 2009)
The use of natriuretic peptides in the neonatal population is emerging. B-type Natriuretic Peptide (BNP) and N-terminal-Pro-BNP (NTpBNP) are used in the adult population to assess myocardial function and volume loading. Their role in prognosis following cardiac surgery has also been identified. In preterm infants NTpBNP is becoming increasingly recognised as a potential screening tool for patent ductus arteriosus (PDA), and a marker for myocardial performance. In addition, NTpBNP may provide prognostic information in preterm infants and term infants with congenital diaphragmatic hernia (CDH). In this paper, the role of NTpBNP in the preterm population will be discussed.